A new method to compensate impedance artefacts for Li-ion batteries with integrated micro-reference electrodes - Raijmakers, L.H.J.; Lammers, M.J.G.; Notten, P.H.L. (Electrochimica acta, 2018)
In order to measure the electrochemical characteristics of both electrodes inside Li-ion batteries, micro-reference electrodes (μREF) turned out to be very useful. However, measuring the electrochemical impedance with respect to μREF can lead to severe measurement artefacts, making a detailed analysis of the impedance spectra complicated. In the present work a new method is developed in which high-frequency measurement artefacts can be compensated. A theoretical analysis, using equivalent circuit models of the measurement setups, shows that if two different impedance measurements are averaged, the impedance contributions from the measurement leads can be completely eliminated. The theoretical analysis is validated using Li-ion batteries with seven integrated μREF, having all different impedances. The measurement results show that artefacts are dominating for high-impedance μREF in the high frequency range. However, these artefacts can be fully compensated by averaging two separate impedance measurements, as predicted by theory. This easily makes it possible to perform artefact-free impedance measurements, even at high frequencies. •A new method is proposed to compensate impedance artefacts.•Artefacts can be compensated by averaging two separate impedance measurements.•Measurement leads and high-impedance reference electrodes contribute to artefacts.•Measurement lead impedance contributions can be fully compensated.•Impedance artefact models are in good agreement with measurements.